2017
DOI: 10.11613/bm.2017.036
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of new Beckman Coulter 25(OH) Vitamin D assay and potential improvement of clinical interpretation

Abstract: IntroductionThe aim of this study was to assess the analytical performances of the newly developed Access2 25-hydroxyvitamin D (25(OH)D) total immunoassay on two analysers, DxI800 and Access2 (Beckman Coulter, Brea, CA, USA), and compare these two and a recalibrated Modular E 170 25(OH)D assay (Roche Diagnostics, Penzberg, Germany) with reference liquid chromatography tandem-mass spectrometry (LC-MS/MS) with special emphasis on clinical diagnosis.Materials and methodsBeckman immunoassays were assessed for impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 23 publications
(23 reference statements)
1
21
0
Order By: Relevance
“…Also, clinically 25 (OH) D concentrations <50.0 nmol/L (< 30 ng/ml) indicate vitamin D deficiency; thus, inaccuracies at low concentrations have a limited impact on treatment decisions. These results are consistent with the findings of previous studies (Madenci et al, 2017;Kocak et al, 2015).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Also, clinically 25 (OH) D concentrations <50.0 nmol/L (< 30 ng/ml) indicate vitamin D deficiency; thus, inaccuracies at low concentrations have a limited impact on treatment decisions. These results are consistent with the findings of previous studies (Madenci et al, 2017;Kocak et al, 2015).…”
Section: Discussionsupporting
confidence: 94%
“…In a study by Kocak et al, (2015) the Roche Cobas vitamin D total assay method showed a bias of (-14.1%), but in our study it is (-4.22%) observed for the Cobas e601. Madenci et al, (2017) had examined Access 2 25 OH vitamin D assay by Bland-Altman analysis and a negative bias with the reference LC-MS/MS was seen (-19.2%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have evaluated and compared 25(OH)D assays. Though the methods overall correlated well, substantial variability between assays was found [12][13][14][15][16]. Some of these studies were performed early after the initiation of the VDSP initiative where standardization of assays…”
Section: Brief Resumé Of the Resultsmentioning
confidence: 99%